Factors Influencing Cryptocurrency Adoption Among Nigerian University Fintech Entrepreneurs: An UTAUT perspective - I. Ebizie, Promise; D. Nkamnebe; Obinna C. Ojiaku, Anayo (British Journal of Marketing Studies, 2022)
Electronic transactions in the financial sector have continued to surge unprecedentedly around the globe. Governments, politicians, and practitioners around the world have been paying close attention to cryptocurrencies in recent years. Cryptocurrencies, a cutting-edge method of exchanging value without the need for a physical medium, offer a number of potential advantages, including quick transactions, cross-border use, low transaction fees, transparency, high security, anonymity, and privacy. As a result, they are anticipated to bring about a significant revolution in the way money is exchanged in the future. In order to forecast adoption of cryptocurrency among Nigerian University FinTech Entrepreneurs, this study will use the Unified Theory of Acceptance and Use of Technology (UTAUT) paradigm. The population of study was drawn from three major universities in Anambra state. Sample sizes of 323 students were used, out of which 313 questionnaires were correctly filled and returned and were used for the analysis. The findings of the study shows that performance expectancy, effort expectancy and facilitating conditions have a positive relationship with cryptocurrency adoption while there was no relationship established with social influence. This study adds to the expanding body of literature on cryptocurrencies and provides beneficial knowledge to fund managers (investors), enterprises, and individual users (payees) (receiving cryptocurrency as a payment method). Citation: Promise I. Ebizie, Anayo D. Nkamnebe and Obinna C. Ojiaku (2022) Factors Influencing Cryptocurrency Adoption Among Nigerian University Fintech Entrepreneurs: An UTAUT perspective, British Journal of Marketing Studies, Vol. 10, Issue 3, pp.25-37